Feature Crumbs: adapting usage monitoring to continuous software engineering - Johanßen, Jan Ole; Kleebaum, Anja; Paech, Barbara (Product-Focused Software Process Improvement, 2018)
We introduce Feature Crumbs, a lightweight, code-based concept to specify a feature’s run-time characteristics. This enables monitored usage data to be allocated to a feature increment. In addition, we analyze the implications for the overall development process. We outline the reference implementation of a platform for collecting, managing, and assessing feature crumbs. We report an evaluation of both the feature crumb concept and the reference implementation in a university capstone course.